Internal displacement in Burma - Lanjouw, Steven; Bamforth, Vicky; Mortimer, Graham (2000)
The internal displacement of populations in Burma is not a new phenomenon. Displacement is caused by numerous factors. Not all of it is due to outright violence, but much is a consequence of misguided social and economic development initiatives. Efforts to consolidate the state by assimilating populations in government-controlled areas by military authorities on the one hand, while brokering cease-fires with non-state actors on the other, has uprooted civilian populations throughout the country. Very few areas in which internally displaced persons (IDPs) are found are not facing social turmoil within a climate of impunity. Humanitarian access to IDP populations remains extremely problematic. While relatively little information has been collected, assistance has been focused on targeting accessible groups. International concern within Burma has couched the problems of displacement within general development modalities, while international attention along its borders has sought to contain displacement. With the exception of several recent initiatives, few approaches have gone beyond assistance and engaged in the prevention or protection of the displaced. - Reproduced
Keywords: Burma - Economic policy; Burma - Population; Refugees